The protective effect of Prunella vulgaris ethanol extract against vascular inflammation in TNF-α-stimulated human aortic smooth muscle cells - Sun Haeng Park; Hyun Jung Koo; Yoon Young Sung; Ho Kyoung Kim (BMB Reports, 2013)
Atherosclerosis, which manifests as acute coronary syndrome,stroke, and peripheral arterial diseases, is a chronic inflammatorydisease of the arterial wall. Prunella vulgaris, a perennial herbwith a worldwide distribution, has been used as a traditionalmedicine in inflammatory disease. Here, we investigated theeffects of P. vulgaris ethanol extract on TNF-α-induced inflammatoryresponses in human aortic smooth muscle cells(HASMCs). We found that P. vulgaris ethanol extract inhibitedadhesion of monocyte/macrophage-like THP-1 cells to activatedHASMCs. It also decreased expression of intercellular adhesionmolecule-1, vascular cell adhesion molecule-1, E-selectin andROS, No production in TNF-α-induced HASMCs and reducedNF-kB activation. Furthermore, P. vulgaris extract suppressedTNF-α-induced phosphorylation of p38 mitogen-activatedprotein kinase (MAPK) and extracellular signal-regulated kinase(ERK). These results demonstrate that P. vulgaris possesses antiinflammatoryproperties and can regulate TNF-α-inducedexpression of adhesion molecules by inhibiting the p38 MAPK/ERK signaling pathway. [BMB Reports 2013; 46(7): 352-357]